Safety assessment of the ethanolic extract of Gongronema latifolium Benth. leaves: a 90-day oral toxicity study in Sprague Dawley rats - Bassel Al-Hindi; Nor Adlin Yusoff; Mariam Ahmad; Item Justin Atangwho; Mohd Zaini Asmawi; Majed Ahmed Al-Mansoub; Yasser Mahfooth Tabana; Idris Bello; Mun Fei Yam (BMC, 2019)
Abstract Background The leaves of Gongronema latifolium Benth. have long been recognized traditionally as a remedy for a variety of ailments in Africa. This study was conducted to evaluate the safety profile of the ethanolic extract of G. latifolium (GLES) leaves through a repeated dose 90-day oral toxicity study in male and female of Sprague Dawley rats. Methods GLES was orally administered at doses of 250, 500 and 1000 mg/kg/day consecutively for 90 days. Results No behavioral or physiological changes and mortality were observed. GLES did not have a marked impact on general hematological parameters and did not precipitate nephrotoxicity. However, compared to the control, serum triglycerides, total cholesterol and low-density lipoprotein levels were lower and white adipose tissue paired retroperitoneal fat depots were depleted in male rats treated with GLES3 by the end of the experiment. The liver was significantly enlarged in GLES-treated rats of both sexes. Negative gender-specific alterations were observed with the highest dose. Adverse risk was evident in the female rats mainly due to marked body weight gain and cerebrum weight reduction. Conclusion Further research is needed to reach more specific conclusions about to the safety of ingesting high doses of GLES for long periods of time.